Advances in bevacizumab in colorectal cancer: a bibliometric analysis from 2004 to 2023 - Chen, Hao; Lei, Yeqing; Zhou, Junjie; Lv, Chenhui; Xuan, Qijia (Frontiers in Oncology, 2025)
BackgroundBevacizumab is a primary focus in the clinical application and research of metastatic colorectal cancer (mCRC) patients. This study aims to analyze publications on bevacizumab and CRC to explore and identify the trends and frontiers of this field.MethodsWe collected 4,164 articles on bevacizumab and CRC from the Web of Science Core Collection (WoSCC). CiteSpace, VOSviewer, R-bibliometrix, and Microsoft Excel were utilized for analysis and visualization.ResultsThe United States, Japan, and China are the leading countries in this field. The National Cancer Institute and the University of Pisa share the top position for the highest number of publications. Personalized therapy, innovative combination treatments, mechanisms of resistance, and new drug development are enduring focal points and future research directions.ConclusionsThis study provides the first bibliometric analysis of research on bevacizumab and CRC, revealing the current status and future directions of this field.